The crystallography of C-centred monoclinic to body-centred tetragonal polymorphic phase transformation in mixed-phase TiO2(B) and anatase nanocomposite. (1st July 2016) - Liu, Hongwei; Zheng, Zhanfeng; Yang, Dongjiang; Zhu, Huaiyong; Zhou, Cuifeng; Liu, Zongwen
Abstract: A detailed invariant line analysis was described on the habit plane and orientation relationship between TiO2 (B) and anatase in titania nanocrystalline photocatalyst. It is demonstrated that the predicted habit plane and orientation relationship are coincident well with the observed crystallographic features. The polymorphic phase transformation of C-centred monoclinic structure to body-centred tetragonal structure is proposed to start from an initial Bain lattice correspondence that close-packed plane of matrix is parallel to close-packed plane of product, so is closed-packed direction. Graphical abstract: A possible transformation mechanism was proposed that the closed-packed plane (001) and closed-packed vector [010] of C-centred monoclinic structure keeps invariant in orientation when transforming into body-centred tetragonal structure.